Carey, Laura (audio interview #1 of 1) - Carey, Laura (7/1908 - 2/1983); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - Laura Carey was interviewed in her home in west Long Beach. Although she was retired, she still kept a neat and apparently well organized house and took care of her family's needs. The interview was cut short when her husband, Red, returned home. The interviewer was the daughter of friends of the Carey's. 2/19/1979